A Simple and Non‐Destructive Method for Assessing the Incorporation of Bipyridine Dicarboxylates as Linkers within Metal–Organic Frameworks. Issue 11 (2nd February 2016) - Hendon, Christopher H.; Bonnefoy, Jonathan; Quadrelli, Elsje Alessandra; Canivet, Jerome; Chambers, Matthew B.; Rousse, Gwenaelle; Walsh, Aron; Fontecave, Marc; Mellot‐Draznieks, Caroline
Abstract: As a novel avenue for applications, metal–organic frameworks (MOFs) are increasingly used for heterogenizing catalytic molecular species as linkers into their crystalline framework. These multifunctional compounds can be accessed with mixed linkers synthesis or postsynthetic‐exchange strategies. Major limitations still reside in their challenging characterization; in particular, to provide evidence of the genuine incorporation of the functionalized linkers into the framework and their quantification. Herein, we demonstrate that a combination of computational chemistry, spectroscopy and X‐ray diffraction allows access to a non‐destructive analysis of mixed‐linker UiO‐67‐type materials featuring biphenyl‐ and bipyridine‐dicarboxylates. Our UV/Vis‐based methodology has been further applied to characterize a series of Rh‐functionalized UiO‐67‐type catalysts. The proposed approach allows a recurrent key issue in the characterization of similar supported organometallic systems to be solved. Abstract : A close combination of computational chemistry, spectroscopy and laboratory X‐ray diffraction allows access to a high‐precision and non‐destructive analysis of the genuine linker's incorporation into mixed‐linker metal–organic frameworks (see figure; bipydc=2, 2′‐bipyridinedicarboxylate; bpdc=biphenyldicarboxylate). The UV/Vis‐based methodology has been further applied to characterize post‐synthetically functionalized catalysts.